Wireless communications with hybrid solar and RF energy harvesting. (2nd June 2023) - Alhamad, Raed I.
Energy harvesting consists to use different source of powers such as radio frequency (RF) signals, the sun and the wind. The harvested energy can be used to recharge the battery of the source used for wireless communications. In this paper, we derive the throughput of wireless communications when the source harvests energy using a solar panel as well as RF signals. We compute the performance when the source uses hybrid energy harvesting using solar energy and RF signals. We derive the signal to noise ratio (SNR) and signal to interference plus noise ratio (SINR) statistics to deduce the packet error probability (PEP) and the throughput. Harvesting duration is optimised to maximise the throughput. We show that the harvested power from RF signals is proportional to the squared absolute value of the channel coefficient. The harvested power from the sun is proportional to the radiation intensity.